Factors Known to Influence the Development of Necrotizing Enterocolitis to Modify Expression and Activity of Intestinal Alkaline Phosphatase in a Newborn Neonatal Rat Model - Rentea, Rebecca Maria; Rentea, Matthea J.; Biesterveld, Ben; Liedel, Jennifer L.; Gourlay, David M. (European Journal of Pediatric Surgery, 2019)
Introduction Prematurity, formula feeding, and early weaning strongly influence enterocyte differentiation. Intestinal alkaline phosphatase (IAP), an endogenous protein expressed in the intestines, is one enzyme that is affected by these factors. IAP supplementation decreases the severity of necrotizing enterocolitis (NEC) injury. We, therefore, hypothesized that prematurity predisposes this population to NEC due to IAP deficiency and investigated IAP expression and function in a neonatal rat model.Materials and Methods Pre- and full-term newborn Sprague-Dawley rat pups were sacrificed on consecutive days of life both after vaginal or cesarean birth and following either breast or formula feeding.Results Compared with controls, cesarean delivery and formula feeding are associated with lower levels of IAP. The formula-fed pups continued to have low baseline IAP activity. Neither prematurity nor formula feeding led to differences of intestinal injury.Conclusion Prematurity and formula feeding are associated with inhibition of IAP expression and activity. Both may increase the risk of NEC and early enteral supplementation of IAP to newborns at risk of NEC may be of therapeutic benefit.
Keywords: intestinal alkaline phosphatase; necrotizing enterocolitis; prematurity; breast milk; alkaline phosphatase